Investigation of Cryptosporidium spp. in breeding nucleus of capuchin monkeys (Sapajus spp.) (Research, Society and Development, 2021)
Animals of the primate order are highly susceptible to parasitic infections due to their social organization, often in groups and interaction between individuals, facilitating the transmission of pathogenic agents, and may be even more prevalent in areas modified by anthropic action. The occurrence of the protozoan Cryptosporidium spp. in wildlife animals in captivity or free-living it characterizes great importance of Public Health mainly for its zoonotic potential. This parasite has a cosmopolitan distribution, causes gastrointestinal infection, and its transmission occurs via the fecal-oral route, either through water or through contaminated food. Cryptosporidiosis affects mammals, birds, reptiles and fish, this significant zoonotic potential, in addition to being directly related to the living conditions of the host and the quality of the environment. We investigated the occurrence of Cryptosporidium spp. in primates located at the Tufted Capuchin Monkey Procreation Center (School of Dentistry of Araçatuba - UNESP). Fecal samples from 49 asymptomatic primates of the species Sapajus spp. species were collected below their individual cages, the soil was lined with a plastic bag, thus hindering environmental contamination. The search for oocysts was carried out using the technique of Negative Malachite Green Staining, finding negativity in all samples examined, which suggests the absence of the protozoan Cryptosporidium spp. in primates studied in the breeding center of capuchin monkeys (Sapajus spp.), noting that they were asymptomatic.